SERANGAN DAN POPULASI Scotinophara sp. PADA TANAMAN PADI SAWAH DI KABUPATEN BOLAANG MONGONDOW TIMUR - Kila, Alex Hendra; Salaki, Ch. L.; Meray, Elisabeth R.M. (EUGENIA, 2016)
ABSTRACT Â  The research aimed to find out the attacks and pest populations Scotinophara sp. in rice crops have been carried out in EastBolaang Mongondow from July to October 2014. The study used survey methods at several centers of rice cultivation in East Bolaang Mongondow, then set three districts as a test site where sampling. Sampling using Method Diagonal slices then select ten clump of rice plants in each sub-sample plots. Samples were taken at vegetative stage and generative phase. Things were observed in this study is the percentage of infected plants and pest populations. The results showed that the highest percentage of infected rice plants in the age of the plants 8 weeks after plants are found in Sub Tutuyan amounted to 66.66 percent and the lowest sequentially the District Nuangan and the District Kotabunan namely 39.33 percent and 11.13 percent.The highest Scotinophara sp. population density was found based on the location is district Tutuyan 10,11 tail and the lowest sequentially District Nuangan and the District Kotabunan is 1.82 and 0.96 tail. The density of the population by age of the plant, the highest in the plant age 8 mst 12.75 and the lowest sequentially 6, 4 and 2 mst is4.38, 0.06 and 0 tail. Keywords : attack, population, Scotinophara sp., rice plant